Social Justice and Poverty: Islamic Economic Perspective - Meirison, Meirison; Unani, Tuti; Kasmidin, Kasmidin (Institut Agama Islam Negeri Kendari, 2022)
This paper aims to describe the socio-economic justice concept taught by Islam, which wants a proportional income distribution. It can also be said that the Islamic economy is an economy based on togetherness. Therefore, it is not strange if the assumption of the Islamic socio-economic justice principle is similar to the socialist system. There has even been an opinion stating that if the socialist system is added and incorporated Islamic elements into it, it will become Islamic. I conducted a literature study and a descriptive analysis approach to the literature and existing sources. Some perspectives and opinions stated that the similarity of the socio-Islamic justice system with socialism was not entirely true; there were more mistakes. The economic principle of socialism, which rejects individual ownership and wants an even income distribution, differs from Islamic economic principles. Islamic economics, the enforcement of socio-economic justice, is based on a sense of brotherhood (ukhuwah), mutual love (mahabah), shoulder to shoulder (takaful), and mutual help (ta'awun), both between the rich and the poor and between the rulers and the people.